Analysis the key to improving organization and individual performance - Swanson, Richard A. 1942-; Chermack, Thomas J. (Routledge, 2025)
"With the volatile nature of today's workplaces, analysis tools are more valuable than ever: this book provides those tools, to capture human expertise before it leaves the organization. The concepts of analysis may be timeless, but recent years have seen massive changes in terms of organizational structures, work systems, and worker requirements, such as remote working and increased employee turnover. This book covers the theory and concepts behind performance improvement, and then turns to the real-world work of performance diagnosis, process improvement, and task documentation, introducing cross-functional task analysis, which recognizes the changing nature of work as more of today's tasks are extensive and require collaboration across jobs. Each chapter can stand alone if organizations need to focus on a particular area, and includes examples that reflect contemporary work, from job descriptions to task inventories and specific task analyses. One of the only texts providing the tools and processes necessary to analyze workplace performance, document human expertise, and develop training materials, this book is intended for managers, executives, students, and any workplace or organization development professional interested in human expertise and how to manage it"--
Includes bibliographical references and index
2412
Keywords: Employees / Rating of; Personnel management; Job evaluation; Performance standards